Perceived Legitimacy and Motivation Effects of Authority - Holger Herz; Christian Zihlmann (Center for Economic Studies and ifo Institute (CESifo), 2024)
Organizational structures are an important determinant of individual incentives and thus individual motivation in organizations. We study whether their effects on individual motivation go beyond incentives and how they relate to the perceived legitimacy of organizational structure. To this end, we design a laboratory experiment in which we exogenously manipulate the organizational structure in a way that leaves the incentives of all individuals unaffected, but changes the perceived legitimacy of the organizational structure. Our data show that organizational structure indeed affects behavior beyond monetary incentive effects and that the observed changes are significantly associated with changes in perceived legitimacy.
Keywords: D01; D23; D91; M50; 330; legitimacy; organization; motivation